Urban Governance as a Foundation of Sustainable Tourism Development: The Case of Wiener Neustadt - Langerné Varga, Zsófia (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper analyses sustainability-driven digital transformation in medium-sized European cities through a case study of Wiener Neustadt, applying the SMART TOUR (Interreg Europe) framework. Based on a structured review of sustainable tourism, smart cities, and destination governance literature, digital transformation is conceptualised as a governance-led strategic process rather than a purely technological shift. The study employs qualitative policy and strategic document analysis, focusing on the STEP WN 2030 urban development strategy and the Klimaneutral 2040 climate strategy. It examines how these frameworks integrate digitalisation, sustainability, and tourism objectives, and how digital tools support resource efficiency, performance monitoring, and stakeholder engagement. The paper contributes to the discussion on smart tourism and sustainable urban development by suggesting how smart tourism models may be applied beyond mass tourism contexts and highlighting secondary cities as key arenas for sustainability-oriented digital transformation, offering context-specific insights with potential relevance for policymakers.